Late Quaternary variability of hydrography and weatheringinputs on the SW Iberian shelf from clay minerals and theradiogenic isotopes of neodymium, strontium and lead - Stumpf, Roland (2011)
The radiogenic isotope systems of neodymium (Nd), strontium (Sr) and lead (Pb) have been used in numerous studies throughout the last decades to investigate water mass circulations of the past and present oceans, and to trace changing contributions of detrital material from different source areas. Clay mineral assemblages and clay mineral ratios from the fine fraction of marine sediments have also been used to characterize endmember sources. This thesis focuses on a reconstruction of the late Quaternary hydrographic variability of the flow path of the Mediterranean Outflow Water (MOW) and the changing weathering contributions of the detrital clay‐size fraction to the SW Iberian shelf. Mediterranean Outflow Water is characterized by higher temperatures and salinities than other ambient water masses. MOW spreads at water depths between 500 and 1500 m from the Strait of Gibraltar into the eastern North Atlantic and has been a source of salinity for the Atlantic Meridional Overturning Circulation in the North Atlantic. In order to evaluate the hydrographic changes of MOW since the Last Glacial Maximum (LGM) high‐resolution Nd and Pb isotope records of past ambient seawater obtained from authigenic ferromanganese oxyhydroxide coatings of bulk marine sediments from three gravity cores in the Gulf of Cadiz (577 m water depth) and along the Portuguese margin (1 745 m and 1 974 m water depth) were produced. The surface and downcore Nd isotope data from all water depths exhibit only a very small variability close to the present day composition of MOW but do not reflect the present day Nd isotopic stratification of the water column as determined from a nearby open ocean hydrographic station. In contrast, the Pb isotope records show significant and systematic variations, which provide evidence for a significantly different pattern of the MOW pathways between 20 000 and 12 000 years ago compared with the subsequent period of time. The assemblages of marine sediments on the SW Iberian shelf consist of the various regional ...